Konsep Garapan Tari Putri Langgok - Murni, Tri (PPSDP Undergraduate Journal of Educational Sciences, 2025)
A work formed from a legend in Payuputat village, Prabumulih, namely the legend of Puteri Lambu Ayu. The author interprets the events of the legend of Puteri Lambu Ayu. The concept of a dance work is a framework that contains the parts that make up a dance work. The concept of a dance work is composed of ideas, title, theme, movements, dancers, floor patterns, make-up, clothing, dance music, stage design and lighting. The working method used is a dramatic and traditional element. The ideas obtained were obtained from the exploration stage which were then developed into a series of various movements for each scene. The purpose of this writing is to facilitate understanding of the dance work “Puteri Langgok” because the choreographer wants the audience, audience and dancers to be able to understand the dance work “Puteri Langgok” visually and in writing.